Electron Transfer Mediated by Iron Carbonyl Clusters Enhance Light‐Driven Hydrogen Evolution in Water by Quantum Dots. Issue 12 (8th May 2020) - Li, Chuanshuai; Rahaman, Ahibur; Lin, Weihua; Mourad, Hassan; Meng, Jie; Honarfar, Alireza; Abdellah, Mohamed; Guo, Meiyuan; Richmond, Michael G.; Zheng, Kaibo; Nordlander, Ebbe
Abstract: Photocatalytic water splitting has become a promising strategy for converting solar energy into clean and carbon‐neutral solar fuels in a low‐cost and environmentally benign way. Hydrogen gas is such a potential solar fuel/energy carrier. In a classical artificial photosynthetic system, a photosensitizer is generally associated with a co‐catalyst to convert photogenerated charge into (a) chemical bond(s). In the present study, assemblies consisting of CdSe quantum dots that are coupled with one of two molecular complexes/catalysts, that is, [Fe2 S2 (CO)6 ] or [Fe3 Te2 (CO)9 ], using an interface‐directed approach, have been tested as catalytic systems for hydrogen production in aqueous solution/organic solution. In the presence of ascorbic acid as a sacrificial electron donor and proton source, these assemblies exhibit enhanced activities for the rate of hydrogen production under visible light irradiation for 8 h in aqueous solution at pH 4.0 with up to 110 μmol of H2 per mg of assembly, almost 8.5 times that of pure CdSe quantum dots under the same conditions. Transient absorption and time‐resolved photoluminescence spectroscopies have been used to investigate the charge carrier transfer dynamics in the quantum dot/iron carbonyl cluster assemblies. The spectroscopic results indicate that effective electron transfer from the molecular iron complex to the valence band of the excited CdSe quantum dots significantly inhibits the recombination of photogenerated charge carriers, boosting the photocatalytic activity for hydrogen generation; that is, the iron clusters function as effective intermediaries for electron transfer from the sacrificial electron donor to the valence band of the quantum dots. Abstract : Iron clusters for electron transfer : An assembly consisting of CdSe quantum dots and [Fe3 Te2 (CO)9 ] has been tested as a catalytic system for proton reduction in aqueous solution. Transient absorption and time‐resolved photoluminescence spectroscopies indicate that the iron cluster functions as an effective intermediary for electron transfer from a sacrificial electron donor to the valence band of the quantum dots.